2020
DOI: 10.1007/s12178-020-09604-4
|View full text |Cite
|
Sign up to set email alerts
|

Operative Versus Non-operative Management of Mid-diaphyseal Clavicle Fractures in the Skeletally Immature Population: A Systematic Review and Meta-analysis

Abstract: Purpose The purpose of this study is to compare the outcomes and complications of operative vs non-operative management of mid-diaphyseal clavicle fractures in the skeletally immature population. Recent Findings Traditionally, skeletally immature clavicle fractures have been managed non-operatively. However, there has been an increasing trend towards operative management with a lack of evidence indicating its effectiveness. Methods Two reviewers searched three online databases (MEDLINE, EMBASE and PubMed), ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
(92 reference statements)
1
12
0
Order By: Relevance
“…The lack of nonunions in this cohort is consistent with the low rate reported in these meta-analyses (nonunion rates of <1% to 2% for nonoperative management and <1% to 3% for operative management 7 , 8 ). The refracture rates of 5% in the operatively treated group and 3% in the nonoperatively treated group are in keeping with previously reported rates of 0% to 8.7% 7 , 8 . Our implant removal rate of 19% is in keeping with the previously reported rate of 15% 7 .…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The lack of nonunions in this cohort is consistent with the low rate reported in these meta-analyses (nonunion rates of <1% to 2% for nonoperative management and <1% to 3% for operative management 7 , 8 ). The refracture rates of 5% in the operatively treated group and 3% in the nonoperatively treated group are in keeping with previously reported rates of 0% to 8.7% 7 , 8 . Our implant removal rate of 19% is in keeping with the previously reported rate of 15% 7 .…”
Section: Discussionsupporting
confidence: 89%
“…Although Constant scores were significantly higher in operatively treated patients, all patients demonstrated favorable scores compared with the general, uninjured population. In their meta-analysis of 7 studies, Nawar et al reported no difference in time to union, return to activity, or complications between operative and nonoperative management, concluding that there is no significant difference between operative and nonoperative management in the skeletally immature population 8 . The lack of nonunions in this cohort is consistent with the low rate reported in these meta-analyses (nonunion rates of <1% to 2% for nonoperative management and <1% to 3% for operative management 7 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations